2010
DOI: 10.5650/jos.59.89
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Highly Water-repellent Surface by Spontaneous Formation of Double Scale Roughness Pattern

Abstract: Hydrophobic organic-inorganic hybrid composite suspensions were prepared by mixing hydrophobic octylsilyl titanium dioxide particles having average diameter of 35 nm with drying oil or moisture cure room temperature vulcanization silicone gum in volatile silicone. They were spread on a glass plate by using a linear motor coater and an applicator. Spatially periodic stripe patterns parallel to the direction of dragging the applicator were usually generated. The phenomenon is called directional viscous fingering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The linear motor coater used in our previous studies was used for the application of the pseudosunscreen solutions. To analyze the pure influence of the geometric factor generated by the viscous fingering on the UV transmission, no roughened PMMA plate for the current in vitro measurements was used, but a flat square quartz plate of 10 cm × 10 cm and a thickness of 3.1 mm was employed as a substrate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The linear motor coater used in our previous studies was used for the application of the pseudosunscreen solutions. To analyze the pure influence of the geometric factor generated by the viscous fingering on the UV transmission, no roughened PMMA plate for the current in vitro measurements was used, but a flat square quartz plate of 10 cm × 10 cm and a thickness of 3.1 mm was employed as a substrate.…”
Section: Methodsmentioning
confidence: 99%
“…Viscous fingering patterns are generated at the moving interface when it becomes unstable to morphological fluctuations . Spatially periodic stripe patterns are spontaneously formed when two pieces of adhesive tape that are stuck together are peeled and a viscous fluid is applied on a solid substrate . Intensity of transmitted UV light passing through the sunscreen layer are varied by the surface shape generated by the viscous fingering, even though the amount of the sunscreens applied per unit area on the substrate is identical.…”
Section: Introductionmentioning
confidence: 99%
“…The linear motor coater used in our previous study [24,25] was used for the application of the pseudo-sunscreen composite onto a flat square quartz plate with a side length of 10 cm and a thickness of 3.1 mm. In current in vitro measurements [26,27,28], the use of rough polymethylmethacrylate (PMMA) plate is stipulated.…”
Section: Methodsmentioning
confidence: 99%
“…The characteristic length of the spatial periodicity corresponds to the wavelength of the fastest growing fluctuation. We found that the stripe pattern was spontaneously formed by the directional viscous fingering during the application of viscous fluid on a glass plate, and we analyzed the influence of the coating condition on the geometry of the surface [24,25]. …”
Section: Introductionmentioning
confidence: 99%
“…They were applied onto a quartz plate and iso-propanol was evaporated. To prevent the pattern formation by the viscous fingering during the application [19][20][21], four-sided applicator was used [22,23]. The gap between the quartz plate and the face of the applicator was 35-45 lm, and the coating velocity was 10 mm s À1 .…”
Section: Measurement Of Uv Absorbance Distributionmentioning
confidence: 99%